2007
DOI: 10.1021/jp068440l
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Isotope Effect on the Atomic Orbital Alignment Dependence in the Reaction of the Oriented Ar (3P2) with CH3CN (CD3CN)

Abstract: Atomic orbital alignment effect was observed for the CN (B2Sigma+) formation in the reaction of oriented Ar (3P2) with CH3CN (CD3CN). The relative cross-sections for each magnetic MJ' substrate in collision frame sigmaH|MJ'| for CH3CN and sigmaD|MJ'| for CD3CN, were determined to be sigmaH0:sigmaH|1|:sigmaH|2|:sigmaD0:sigmaD|1|:sigmaD|2| = 1.00:0.81:0.84:2.01:1.92:1.87. A significant atomic orbital alignment effect was observed. In addition, a notable deuterium isotope effect was observed on both the cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Details of the experimental apparatus and the procedure were described elsewhere, ,, and only an outline is given here. An almost pure Ar ( 3 P 2 , M J = 2) beam (more than 93%) was generated by using an inhomogeneous magnetic hexapole .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the experimental apparatus and the procedure were described elsewhere, ,, and only an outline is given here. An almost pure Ar ( 3 P 2 , M J = 2) beam (more than 93%) was generated by using an inhomogeneous magnetic hexapole .…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the effects of the deuterium isotope on the atomic alignment effect, we tested the earlier proposal that the reaction of the 2e orbital was responsible for the increase in cross-section with deuteration, and we suggested that the expectation of the static anisotropy for the orbital overlap efficiency between the 2e and 3p orbitals is inadequate to explain the deuterium isotope effect on both the atomic alignment and the molecular orientation dependence. In addition, some configurational correlations between the atomic alignment and the molecular orientation were proposed …”
Section: Introductionmentioning
confidence: 99%
“…It has been well recognized that the alignment of the electron spin in the collision frame gives little effect on the dynamics as the Percival–Seaton hypothesis . Indeed, it has been reported that the atomic alignment effects on the most reaction processes are simply controlled by the configuration of the orbital angular momentum without spin effect ( L -dependence). However, the breakdown in the Percival–Seaton hypothesis (i.e., the importance of the spin-dependent interaction) infrequently has been reported. , We also experimentally observed the breakdown in the Percival–Seaton hypothesis ( J -dependence) in a few Ar ( 3 P 2 ) reactions. , Although it is not obvious that the Percival–Seaton hypothesis is of general relevance for the two-electron process on the triplet species involving two unpaired electron spins like Ar ( 3 P 2 , 4s [3/2] 2 ), in which the angular momentum of ion core (unpaired 3p orbital) weakly couples with the unpaired electron spin of 4s orbital, a negligible rank 4 moment (no spin alignment effect) has been observed in the most studies on the energy transfer reaction of oriented metastable rare-gas with small molecules. According to the Percival–Seaton hypothesis, the dynamics of Ar ( 3 P 2 ) reaction is dominantly controlled by the configuration of the half-filled Ar (3p) orbital of Ar ( 3 P 2 ) in the collision frame. In other words, the atomic alignment effect in the Ar ( 3 P 2 ) reaction can be represented by the moments up to rank 2 ( a 2 ), because the physics of the process is dominantly determined by the orbital angular momentum L (= 1) and its components M L ′ in the collision frame.…”
Section: Discussionmentioning
confidence: 64%
“…The reaction of metastable rare gas with small molecules has been widely studied as a benchmark system for the energy transfer process which is important as a fundamental process for chemical reactions such as initial steps in the photosynthetic process . The importance of molecular orientation linked with the spatial distribution of molecular orbital has been experimentally recognized in our laboratory. Recently, we developed an oriented Rg* ( 3 P 2 , M J = 2) beam and applied it to the energy transfer reactions. The significant atomic orbital alignment effects were recognized in the energy transfer reactions. Especially, we proposed that the alignment of the angular momentum of the ion core in the collision frame is conserved in the course of reaction process …”
Section: Introductionmentioning
confidence: 99%
“…That is, no spin alignment effects result in no contribution of the rank 4 moment because J (2) is not the proper quantum number to describe the essential dynamics in this case. Although it is not obvious that this kind of stereoselectivity is of general relevance even for the triplet species, we have observed a negligible rank 4 moment (no spin alignment effect) in the most studies on the energy transfer reaction of oriented metastable rare-gas with small molecules. …”
Section: Introductionmentioning
confidence: 67%